2014
DOI: 10.1063/1.4865220
|View full text |Cite
|
Sign up to set email alerts
|

Nudged-elastic band used to find reaction coordinates based on the free energy

Abstract: Transition paths characterize chemical reaction mechanisms. In this paper, we present a new method to find mean reaction paths based on the free energy. A nudged elastic band (NEB) is optimized using gradients and Hessians of the free energy, which are obtained from umbrella integration. The transition state can be refined by a Newton-Raphson search starting from the highest point of the NEB path. All optimizations are done using Cartesian coordinates. Independent molecular dynamics (MD) runs are performed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…Furthermore, we showed that by using an a posteriori statistical analysis (33) one can also establish the reliability of the kinetics thus generated. The use of metadynamics for obtaining kinetic information is still in its infancy, however its usefulness has been tested by us and other groups in a range of systems (15,(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Furthermore, we showed that by using an a posteriori statistical analysis (33) one can also establish the reliability of the kinetics thus generated. The use of metadynamics for obtaining kinetic information is still in its infancy, however its usefulness has been tested by us and other groups in a range of systems (15,(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Therefore, a second group of methods founded on TPT implement the chain-of-states approach, which assumes that the transition path can be meaningfully encoded as a series or chain of structures (also referred to as images) [ 342 , 607 , 620 623 ]. These methods can track an arbitrary number of progress coordinates while restraining sampling to effectively one dimension.…”
Section: Categorization By Algorithmic Frameworkmentioning
confidence: 99%
“…Generally, NEB methods require that the energy landscape be relatively smooth and are not effective on rugged energy landscapes [ 619 ]. Remedies have been proposed by having NEB methods operate on the free energy landscape [ 623 ], which is expected to be smoother, or by introducing temperature corrections to the MEP [ 626 ]. Caution must be exercised not to double count entropy when operating on free energy landscapes.…”
Section: Categorization By Algorithmic Frameworkmentioning
confidence: 99%
“…This methodology requires the identification of minimum energy paths (MEPs) that are traversed between pristine and defected states of the material, including the saddle point that characterizes the lowest energy barrier between these states. Techniques such as the nudged-elastic band (NEB) method can be used for such purposes, as was done by Zhu and Li 43 and by Bohner et al 44 Nguyen et al have also used the example of dislocation nucleation at crystal surfaces to study the strengths and limitations of several TST approaches, 45 including both harmonic (hTST) and quasiharmonic approximations of TST as well as a variational-based formulation (VTST). Their results provide physical insight on both the nucleation process at room temperature, and its rate sensitivity.…”
mentioning
confidence: 99%